DNA methylation of the LEP gene is associated with craving during alcohol withdrawal. (January 2015) - Hillemacher, Thomas; Weinland, Christian; Lenz, Bernd; Kraus, Thomas; Heberlein, Annemarie; Glahn, Alexander; Muschler, Marc A.N.; Bleich, Stefan; Kornhuber, Johannes; Frieling, Helge
Highlights: We investigated DNA methylation patterns of the leptin gene promoter region in alcohol dependent patients. Low methylation status is associated with increasing serum leptin levels during withdrawal. low methylation status is associated with an elevation of alcohol craving during withdrawal. Summary: Different studies have described evidence for an association between leptin serum levels and craving in alcohol dependent patients. As leptin expression is regulated by DNA methylation we investigated changes of DNA methylation of the LEP gene promoter region in alcohol dependent patients undergoing withdrawal. Results show that low methylation status is associated with increasing serum leptin levels and elevation of craving for alcohol in the referring patients group. These findings point towards a pathophysiological relevance of changes in DNA methylation of the LEP gene promoter region in alcohol dependence.